TRAINING IN MANUFACTURING VARIANTS OF TRADITIONAL ACEHIAN SWEETS AND MAKING WELCOME DRINKS - Marlina, Marlina; Yanti, Ira Dama; Nanda, Riska; Yeni, Manovri; Agustina, Maya (Universitas Muhammadiyah Aceh, 2024)
Aceh has a very diverse culture and tradition. There are many interesting things to learn about Acehnese traditional foods and how welcome drinks are made. Keumamah, also known as reuboh, boh leukat, timphan, and seunarah, is a traditional Acehnese food passed down from generation to generation. The main ingredients used, such as glutinous rice flour, coconut milk, and palm sugar, show the natural richness of Aceh. Welcoming guests with a welcome drink is an Acehnese custom. For respect and hospitality to the Acehnese, drinks such as reuboh, tubruk coffee, and jasmine tea made from natural ingredients are served. The tradition of welcoming guests shows the friendly and warm nature of the Acehnese people. Therefore, the tradition of making welcome drinks and various Acehnese traditional foods is an important part of Aceh's culinary and cultural richness that must be preserved. Acehnese cuisine has a cultural diversity that makes it unique and interesting. Further research on this component can provide deeper insight into Aceh's culinary heritage and efforts to preserve this tradition. Welcome drink-making course and Acehnese specialties for special events the training venue was the Kampong Rimo hall in Gunung Meriah District, Aceh Singkil Regency. The event was attended by 12 mothers of Family Empowerment and Welfare (PKK) from Kampong Rimo, Gunung Meriah District, Aceh Singkil Regency. Keywords: Typical Acehnese snacks, welcome drinks, special occasion events